Analysis of The Effect of Health and Safety (K3) On Performance with Job Satisfaction as An Employee Intervening Variable - Amaliyah, Aam; Kusdino , Dede; Hidayat , Satria; Solahudin , Ade (Publikasi Indonesia, 2024)
Employee performance is one of the key factors for the company's success. Employees who have good performance can help the company achieve its goals more effectively and efficiently. This study aims to analyze the effect of occupational health and safety (K3) on employee performance by considering the level of job satisfaction at PT. Indocement Tunggal Prakarsa Tbk. The research method uses a quantitative approach with questionnaires as data collection instruments. The collected data is then analyzed using regression tests using the SPSS program. The results showed that there was a significant positive influence between K3 on employee performance. In addition, there is a significant positive influence between K3 on job satisfaction. The results showed that safety, health and job satisfaction affect employee performance. In addition, work safety also affects employee job satisfaction. In addition, there is a significant influence of work safety on performance with satisfaction as an intervening variable. Later, occupational health was found to affect performance with job satisfaction as an intervening variable.